1995
DOI: 10.1007/bf00019190
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and expression analysis of cDNA clones encoding a small and a large subunit of ADP-glucose pyrophosphorylase from sugar beet

Abstract: The cDNA cloning of a small and a large subunit of ADP-glucose pyrophosphorylase (AGPase) from sugar beet is reported. The deduced amino acid sequences are highly homologous to previously identified AGPase polypeptides from other plant species. Both subunits are encoded by low copy genes. When RNA gel blot experiments were performed, strongest expression was detected in sink and source leaves of greenhouse-grown sugar beet plants. A lower expression was found in other tissues tested, i.e. in the hypocotyl, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…RNA gel blot analysis of expression of the large subunit gene of sugar beet indicated that the large subunit and small subunit genes were strongly expressed in sink and source leaves (Müller-Röber et al 1995). A high level of mRNA accumulation for the large subunit gene was observed in the stem of sweet potato, but it was totally absent in the tuber and photosynthetic leaves (Harn et al 2000; Lee et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…RNA gel blot analysis of expression of the large subunit gene of sugar beet indicated that the large subunit and small subunit genes were strongly expressed in sink and source leaves (Müller-Röber et al 1995). A high level of mRNA accumulation for the large subunit gene was observed in the stem of sweet potato, but it was totally absent in the tuber and photosynthetic leaves (Harn et al 2000; Lee et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The only time that the Lys residue of the site s-I was not conserved was in a clone from sugar beet that had a deletion of 12 amino acids in that region. However, this clone has not been expressed to determine if it has any activity and it was used only as a probe in blot experiments (Muller-Rö ber et al, 1995). Another exception is a PCR product from Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…The LS group can be divided into two subgroups corresponding to sink (sites of net sugar import like endosperm, roots, and young leaves) and source (sites of net sugar export like mature leaves) tissues, with the exception of the sugar beet large subunit that is expressed in sink and source leaves (27) and is included in the sink group of LS. Arabidopsis APL1 is considered to be the main isoform expressed in leaves (36).…”
Section: Fig 2 Activation By 3-pga Of the Recombinant Arabidopsis Amentioning
confidence: 99%
“…3, SS genes are expressed in both photosynthetic and nonphotosynthetic tissues, whereas LS genes are expressed preferentially in a tissue-specific manner (9,23,27). Arabidopsis ApL1 is mainly expressed in leaves (36) and, correspondingly, is included in the leaf group of APLs (Fig.…”
Section: Fig 3 Comparison Of Adp-glcmentioning
confidence: 99%
See 1 more Smart Citation